MODELING OF INFLUENCE OF AMPLITUDE-TIME PARAMETERS OF ELECTRICAL PULSES ON ANODE DISSOLUTION PROCESSES IN WIRE ELECTROCHEMICAL MACHINING - О. П. Плахотний (Вісник Черкаського державного технологічного університету, 2018)
Combined technology of sequential use of electroerosive and electrochemical machining with wire electrode allows to obtain highquality surface and to form metal components with high accuracy, regardless of material strength and hardness. Pulsed current in electrochemical machining greatly increases process controllability. The paper provides mathematical model of mass transfer in nearanode diffusion layer. This, together with calculation of current density distribution for a scheme with cylindrical cathode and flat anode, gives reasonable choice of amplitude-time parameters of electrical impulses. Such approach provides maximal current efficiency and precise prediction of removed layer thickness of surface obtained by a moving wire electrode. Conducted experimental researches on approbation of calculated method have shown that theoretical calculations are well consistent with experimental data. Proposed method allows to increase efficiency of electrochemical surface finishing after electroerosive cutting.